“Creative Shifts” as a Means of Measuring and Promoting Translational Creativity - Bayer-Hohenwarter, Gerrit (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
Thanks to Paul Kußmaul, the investigation of translational creativity has made considerable progress. The measurement of creativity, however, has remained a great challenge. The following article presents the results of the measurement of one aspect considered central to the notion of translational creativity, namely the measurement of the ability to depart from the source text (ST) structure by applying creative shifts, i.e., abstracting, modifying or concretising source text ideas in the target text (TT). Sixteen units of analysis from 4 experimental texts translated by 11 students of translation and 5 professional translators each were analysed with the aim of finding out how many of them constituted creative shifts as opposed to mere reproductions of the source text. The results of this sample analysis reveal that there are clear differences between student and professional behaviour and that a certain trend for the development of creative competence can be established. Moreover, these results do not only point to a methodologically interesting approach for analysing complex cognitive constructs, but they also provide a valuable starting point for pedagogic research and application.